Gamifying Collaboration: Enhancing EFL Reading Skills through Kahoot! Application - Nidiya Mawarni; Cut Nadia Muji Rahmah; Puan Maharani (LingPoet: Journal of Linguistics and Literary Research, 2025)
This study explores the effectiveness of Kahoot-based collaborative learning as an instructional strategy to enhance reading skills among English as a Foreign Language (EFL) learners. The research was conducted at Senior High School in Medan with 22 tenth-grade students as participants. Utilizing a Classroom Action Research (CAR) approach, the study was implemented in two cycles, each comprising planning, action, observation, and reflection phases. The data were collected through a combination of quantitative (pre-test and post-test scores) and qualitative (student activity observations and documentation) methods. The pre-test results revealed that none of the students met the minimum passing grade (KKM) of 75, with an average score of 47. In Cycle I, only 31.81% of students surpassed the threshold, with the average score increasing to 70. However, in Cycle II, a notable improvement was observed as 72.72% of students scored above the KKM, raising the average to 80. Furthermore, qualitative findings indicated significant growth in student engagement, participation, and enthusiasm, with student activity levels rising from 55% in Cycle I to 87% in Cycle II. These results demonstrate that integrating the Kahoot application into collaborative learning environments can significantly improve both cognitive outcomes (reading comprehension) and affective factors (motivation and interaction) in EFL classrooms. Kahoot's interactive and gamified nature creates a learner-centered atmosphere that promotes active participation and facilitates deeper comprehension of reading materials. The study concludes that Kahoot is a valuable digital tool to transform traditional reading instruction into a dynamic, engaging, and collaborative experience, thereby contributing to improved literacy outcomes in EFL contexts.